2013
DOI: 10.1007/s11250-013-0501-5
|View full text |Cite
|
Sign up to set email alerts
|

Serological survey and risk factors for brucellosis in water buffaloes in the state of Pará, Brazil

Abstract: To evaluate the prevalence and possible risk factors for brucellosis caused by Brucella abortus in water buffaloes in the state of Pará, Brazil, 3,917 female buffalo serum samples from pregnant and non-pregnant animals were examined: 2,809 from Marajó Island and 1,108 from the mainland. The buffered acidified plate antigen (BAPA) screening test positively diagnosed 4.8% (188/3,917) of the animals with brucellosis, and the 2-mercaptoethanol (2-ME) confirmatory test affirmed 95.7% (180/188) of the results. The b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 8 publications
2
7
0
3
Order By: Relevance
“…Variation in the incidence of infection is related to the course of the diseases, locality, rate of exposure, reproductive status, sex, improvements in the diagnostic techniques and vaccination strategies (Ghazi et al, 2006). It has been reported that the genetic variation within the host may play a part in the resistance to brucellosis (Silva et al, 2013). It has been found that, out of 87(14.03%) aborted buffaloes, 3 (3.45 %) were positive for culture and isolates were identified as B. melitensis biovar 3 (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Variation in the incidence of infection is related to the course of the diseases, locality, rate of exposure, reproductive status, sex, improvements in the diagnostic techniques and vaccination strategies (Ghazi et al, 2006). It has been reported that the genetic variation within the host may play a part in the resistance to brucellosis (Silva et al, 2013). It has been found that, out of 87(14.03%) aborted buffaloes, 3 (3.45 %) were positive for culture and isolates were identified as B. melitensis biovar 3 (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…No Pará os estudos de presença de anticorpos contra Brucella sp. em bubalinos ainda são insipientes, com frequência de anticorpos variando de 3,75% a 4,8 % (Silva et al, 2014a;Silva et al, 2014b;Viana et al, 2009). Em outros estados da federação a situação é semelhante, como em Minas Gerais, Paraíba e Maranhão, com prevalências distintas que variam entre 0 a 37,5% (Bastianetto et al, 2005;Brasil et al, 2015;Carvalho et al, 2015).…”
Section: Introductionunclassified
“…In addition, developed countries in Latin America, Southern Europe, Africa, South and Southeast Asia, and the Middle East, especially in the rural areas, where livestock rearing and production of dairy products and by-products is crucial for family income [2,7,56,[75][76][77][78][79][80].…”
Section: Brucellosismentioning
confidence: 99%
“…The broad management system, challenges for the achievement of sterile control projects that were done nationally for huge herds and broad regional dimension, and the confusion that water buffaloes are highly resistant to disease are factors that thwart those control from claiming brucellosis clinched alongside water buffaloes [92,93].…”
Section: Brucellosismentioning
confidence: 99%
See 1 more Smart Citation